Polbeng Research Vessel Comfort Study in the Malacca Strait - Jamal, Jamal; Santoso, Budhi; Hafiz, Muhammad Alimul; Romadhoni, Romadhoni; Fazrian, Fazrian; B, Siswandi; Jupri, Jupri; Juanda, Juanda (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
The Polbeng Research Vessel is a ship that will be built by Politeknik Negeri Bengkalis (Polbeng) in collaboration with CV. Fatih Bahari Engineering. This vessel is made of High Density Polythene (HDPE) plastic, with the main dimensions of the ship: length (LOA) is 9 metres, breadth (B) is 2.2 metres, height (H) is 1.2 metres, and it uses an 85 HP outboat engine. This vessel's comfort study was conducted to see the ship's performance against equipment and humans in supporting research activities carried out by Polbeng. There are 4 cases in the study where there are 2 wave heights, namely 0.2 metres and 0.4 metres; each wave height is taken from 2 directions of waves hitting the ship, namely the beam seas direction (900) and the head seas direction (1800). There are 3 motions analysed, namely heave, roll, and pitch movements. The results of the ship's motion show that the roll motion in the Beam Seas wave direction has a more significant motion when compared to other motions. The analysis results show that the motion is in accordance with the theory that small ships for roll motions have shorter turnaround arms. Overall, this ship's motion is still common and meets the ship's comfort criteria based on the criteria issued by NORDFORSK 1987, STANAG 4154, U.S. Coast Guard (USCG), ISO 2631/1, ISO 2631/3, and BS. 6841:1987